1990
DOI: 10.3109/00365529008997596
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Absorption after Intestinal Resection: The Importance of a Preserved Colon

Abstract: Calcium absorption was studied in 62 patients with Crohn's disease during a 1-week admission on a standardized diet supplying 70 g fat, 800 mg calcium, and 200 mg oxalate. All patients had been subjected to a distal small-bowel resection of at least 50 cm. Twenty-two had an ileostomy, and 40 had at least half of the colon in function. In all patients the disease was inactive. Calcium absorption was determined by the fractional accumulation in the skeleton of the antebrachium of an intravenous and oral dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Different from the mouse study, 30 these children are slightly hypocalcemic and the low serum calcium levels may also hinder bone mineralization. Other conditions considered to diminish intestinal calcium absorption are reduced gastric acidification 78 and gastrectomy 79 and they may lead to a negative calcium balance.…”
Section: Human Studiesmentioning
confidence: 99%
“…Different from the mouse study, 30 these children are slightly hypocalcemic and the low serum calcium levels may also hinder bone mineralization. Other conditions considered to diminish intestinal calcium absorption are reduced gastric acidification 78 and gastrectomy 79 and they may lead to a negative calcium balance.…”
Section: Human Studiesmentioning
confidence: 99%
“…The highest expression levels of TRPV6 are in the distal intestine (517). Studies from rats and humans show that total calcium absorption is significantly higher when the colon is preserved after extensive small bowel resection (203,491). In addition, we recently showed that transgenic expression of VDR specifically in ileum, cecum, and colon of Vdr null mice is sufficient to prevent the abnormal calcium homeostasis phenotype of Vdr KO mice (86) (FIGURE 4).…”
Section: Vitamin D and The Distal Intestinementioning
confidence: 99%
“…Conservation of the colon is advantageous as it absorbs water, sodium [21][22][23][24][25] , magnesium [25,26] , calcium [27] , short and medium chain fatty acids [28][29][30] , slows gastro-intestinal transit [31] and stimulates small intestinal hyperplasia [32] . Patients with a preserved colon after a small bowel resection may survive without parenteral support with a very short [33,34] or even no remaining jejunum [35] .…”
Section: Colonmentioning
confidence: 99%